TMT-Based Quantitative Proteomic Profiling of Overwintering Lissorhoptrus oryzophilus - Xinxin, Zhang; Shuang, Yang; Xunming, Zhang; Shang, Wang; Juhong, Zhang; Jinghui, Xi (Frontiers in Physiology, 2020)
Adaptations to low temperature play a critical role in restricting the geographical distribution of insects. Decreasing day lengths and temperatures trigger seasonal cold adaptations in insects. These adaptions include changes in expression at the miRNA, mRNA and protein levels. The rice water weevil (RWW), Lissorhoptrus oryzophilus, introduced from the Mississippi River, is a globally invasive pest of wetland rice that can survive at the northern border of China. To investigate the changes in expression at the protein level in overwintering female RWW adults, 6-plex tandem mass tags were used in overwintering and summer adults. Altogether, 1077 proteins were quantified, 183 of which differed significantly between the overwintering and summer samples. To further understand these differentially expressed proteins (DEPs), bioinformatics analyses such as GO enrichment analyses were performed. DEPs associated with the terms binding, structural molecule activity, catalytic activity, multicellular organismal process, extracellular region, chitin binding, metabolic process, intracellular part and organic cyclic compound binding were altered by selection during winter. The changes in the expression of these proteins suggest that the proteins are important for RWW survival in winter.